Analysis of the effect of in vitro dissolution on the pharmacokinetics of albendazole - Nelly Castro; Iliana González-Hernández; Lourdes Mayet-Cruz; José Becerril-Vega; Sergio Soto-Romo; Helgi Jung-Cook (Universidade de São Paulo, 2023)
Abstract Albendazole is an anthelmintic drug commonly used in parenchymal neurocysticercosis and cystic echinococcosis. The aim of this study was to explore whether disparities in the dissolution profiles of albendazole products lead to significant differences in pharmacokinetic parameters. Three generic products and the innovator were evaluated in vitro. Quality control tests were performed, and dissolution profiles were obtained according to the Mexican Pharmacopeia. Although all products passed the quality control tests, none of the generic products complied with the similarity factor (f 2). The product with the lowest f 2 value in respect to the reference was chosen for in vivo evaluation. The study was carried out in 12 healthy volunteers who received 400 mg of the generic or reference product according to a crossover design. No significant differences were found in Cmax and AUC for albendazole and its main metabolite, albendazole sulfoxide, between products. Two absorption peaks were observed in the pharmacokinetic profile, and a population (22%) with different absorption rates and delay time for the the second peak was found. Based on the results, due to the high variability in the absorption process the differences observed in vitro could not be observed in vivo.